2019
DOI: 10.1186/s12879-019-3898-2
|View full text |Cite
|
Sign up to set email alerts
|

The perceived effectiveness of MERS-CoV educational programs and knowledge transfer among primary healthcare workers: a cross-sectional survey

Abstract: BackgroundKnowledge transfer of Middle East respiratory syndrome coronavirus (MERS-CoV) involves the dissemination of created/acquired information on MERS-CoV in hospitals, making this information accessible to all healthcare workers (HCWs). This study evaluated the perceived effectiveness of MERS-CoV educational programs and knowledge transfer among primary care HCWs at a hospital in Saudi Arabia that witnessed the largest outbreak of confirmed MERS-CoV cases in this country.MethodsA survey was distributed am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
3
27
1
3
Order By: Relevance
“…The MOH strives to increase accessibility to health materials and information delivery, with the aim to improve healthcare providers' awareness, perception, and awareness (MOH, 2020) [14]. Aldohyan et al [21] noted that healthcare workers from primary care settings in Saudi Arabia received information through the MOH website. MOH information is considered scientifically reliable, validated, up to date and similar to the mandates of WHO guidelines [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The MOH strives to increase accessibility to health materials and information delivery, with the aim to improve healthcare providers' awareness, perception, and awareness (MOH, 2020) [14]. Aldohyan et al [21] noted that healthcare workers from primary care settings in Saudi Arabia received information through the MOH website. MOH information is considered scientifically reliable, validated, up to date and similar to the mandates of WHO guidelines [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas enough students from 2nd (12%), 3rd (22.5%), 4th (21%), 5th (11%), and 6th (30%) year participated in the survey, only 3.3% of first-year students responded to the questionnaire in the present study. In a study by Aldohyan et al (12), the sample comprised of 404 HCWs, of which 64% were females and 36% were males. Almost 26% were ≤ 30 years old, and 42% had more than 10 years of work experience.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the effectiveness of dissemination of knowledge related to COVID-19 has also been studied by researchers to shed light on proving the accessibility and impact to training programs. However, the existing gap with limited knowledge about emerging infectious disease and infection control practices significantly exists and positively correlates to the insufficient knowledge transfer due to less number of experience and young age [30]. Alsahafi et al [31] also acknowledged that sub-optimal knowledge was found among HCW and recommended the dire necessity of further training and education primarily of personal protective equipment, controlling infections by appropriate measures, and isolation techniques.…”
Section: Training Programmentioning
confidence: 99%